Brazil : Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This report is a detailed assessment of Brazil's compliance with the Basel Core Principles. Brazil has a well-defined banking supervision process that grants the Banco Central do Brasil (BCB) broad enforcement powers to carry out corrective actions. The licensing process has been enhanced, and considerable improvements have been implemented with regards to debt collection by the BCB. The authorities have adopted strategies to improve compliance measures. Corrective and remedial powers of supervisors have been streamlined. Consultations are under way for implementing Basel-III.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet